Pengendalian Kualitas Produk Joint Break Arm di PT. Sandiya Jaya Abadi dengan Metode Six Sigma - Putra, Bagas; Umar, Farhat (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PT Sandiya Jaya Abadi, is a company that focuses on lathe fabrication and engineering, milling/drilling, gtaw (tig), smaw, gmaw welding. This company produces various kinds of bolt components that are in motorcycles. One of them, namely, Joint Break Arm is a connection to the rear brake adjuster on a motorbike. The problems that occur in the Joint Break Arm product are, the size does not match the specified size, the diameter does not match, and the shape of the surface is rough. This study aims to analyze the root causes of product defects and to provide repair solutions for the Joint Break Arm product using the Six Sigma method. This study shows that the DPO value is 3.330791107 and the DPMO is 330791.1. As well as the Six Sigma value of, 4.914390716. From the results of the analysis of these defects, suggestions for improvements are given to reduce the number of these defects. Proposed improvements are: Organizing training to raise awareness of the importance of maintaining product and machine quality; Supervise raw materials before they are stored in the warehouse; Carry out maintenance and repair of machines regularly and continuously (sustainable); Create standard controls for checking tool posts on machines, use life time controls on zigs and create standards for mixing friction media and workpieces; Maintain all core and supporting elements to maintain a well-maintained work environment.